La administración pública y la satisfacción del usuario en el Gobierno Regional de Loreto 2022 - Benzaquen Tuesta, Kadhir (2023)
The present investigation entitled: public administration and user satisfaction in the regional government of Loreto 2022, had the general objective of determining the relationship between public administration and user satisfaction in the Regional Government of Loreto in the year 2022. The type of The research is basic, with a cross-sectional, non-experimental design and was carried out with a sample of 384 residents. It is concluded with a significance value (observed critical value) 0.000<0.05 that the public administration is closely linked to the guarantee of the Loreto Regional Government of user satisfaction in the year 2022.